Perceptual grouping and the bounce–stream illusion - Nihan Alp; Stuart Anstis (i-Perception, 2025)
Two spots moving simultaneously along the same path in opposite directions can appear either to bounce or stream. Bouncing is promoted by spots that turn back and retrace their path. Streaming is promoted by same-size spots, moving along a straight path and viewed peripherally. Both percepts are driven by Gestalt grouping.